2019
DOI: 10.31857/s0002-3515556182-193
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of first mode breather of internal waves above the bottom step in a three-layer fluid

Abstract: In the present study we consider propagation of a localized internal perturbation in the form of an oscillating wave packet (breather) of the first mode in a three-layer fluid with an uneven bottom shaped as a smoothed step. The study is carried out by methods of numerical simulation within a fully nonlinear two-dimensional (vertical plane) set of NavierStokes equations. A set of calculations was carried out for different widths and heights of the bottom step. Inhomogeneity of the medium leads to transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Rouvinskaya et al (2015) investigated shoaling breathers and compared solutions of the Gardner equation, with an additional shoaling term, with fully nonlinear numerical simulations. Lobovikov et al (2019) also undertook numerical simulations to investigate the shoaling of internal wave breathers from a symmetric stratification in deep water to an asymmetric stratification in shallow water and found that two breathers could form in the shallow water if the step was large enough. Energy was also transferred to small-amplitude trailing waves and reflected waves.…”
Section: Introductionmentioning
confidence: 99%
“…Rouvinskaya et al (2015) investigated shoaling breathers and compared solutions of the Gardner equation, with an additional shoaling term, with fully nonlinear numerical simulations. Lobovikov et al (2019) also undertook numerical simulations to investigate the shoaling of internal wave breathers from a symmetric stratification in deep water to an asymmetric stratification in shallow water and found that two breathers could form in the shallow water if the step was large enough. Energy was also transferred to small-amplitude trailing waves and reflected waves.…”
Section: Introductionmentioning
confidence: 99%